Herpetofaunal Diversity of Çanakkale Southwest Coastal Zones - Begüm Boran; İbrahim Uysal; Murat Tosunoğlu (Turkish Journal of Bioscience and Collections)
Along with the literature information obtained from previous studies, the determination of species in herpetofauna studies gives information about the herpetofauna of the research area. Researching the herpetofauna of regions is very important in terms of conservation of species, revealing biodiversity, identifying possible threats, and determining the preventitive measures to be taken against these threats. The study area is the southwestern coastal regions of Çanakkale, which is also the westernmost coast of Anatolia. This area consists of the localities of Ahmetçe, Sazlı, Kozlu, Behram, Bektaş, Koyunevi, Babakale, Gülpınar, Tuzla, Kösedere, and Tavaklı. Because it has the potential to be a coastline separated by the end of the Kaz Mountains, this study area has different habitats and has the potential to host species that exceed isolation of the Kaz Mountains. In this study, the amphibian and reptile diversity of terrestrial and aquatic areas along the coast of Southwest Anatolia starting from the end of the Kaz Mountains, which is the habitat preferences of the species, and the effects of environmental and anthropogenic factors on the herpetofauna of the region were investigated. A total of 5 amphibian species and 16 reptile species have been identified in the southwestern coastal areas of Çanakkale, and the Testudo graeca species are vulnerable according to the IUCN categories.